A Novel Label-Free Biosensor for Detection of HE4 in Urine Based on Localized Surface Plasmon Resonance and Protein G Directional Fixed. (23rd October 2020) - Duan, Ruiqi; Xi, Mingrong
Abstract : A non-invasive and more sensitive method for detection of HE4 is very important for the early screening and detection of ovarian carcinoma. In this study, we improved our previous localized surface plasmon resonance (LSPR) biosensor for detection of HE4 in urine to overcome disadvantages of conventional methods. Protein G directional fixed method was firstly used for LSPR biosensor to improved sensitivity, and standard HE4 and clinical samples were detected separately using this new biosensor. Compared to our previous LSPR biosensor, this new sensor was more sensitive, with other advantages as before. Under optimum conditions, this new biosensor could display a detection limit of 1 pM and wide dynamic range of 1 pM to 10, 000 pM. This new biosensor was effective for detection of HE4 in urine of early ovarian cancer patients, without label and purification. To the best of our knowledge, this is first work to investigate LSPR biosensor for detection of tumor marker in urine, with great advantages and clinical application potentials.